Hermeneutika sebagai Metode Pembebasan: Rekonstruksi Gender dalam Teks Al-Qur’an–Hadis - Anggi Anggraini; Barsihannor B; Muhaemin M (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This paper discusses the relevance of hermeneutics as a method of liberation in reconstructing gender understanding within the texts of the Qur’an and Hadith. Gender issues in Islamic discourse often do not originate directly from the revealed texts, but rather from interpretive traditions shaped by patriarchal social contexts. Therefore, this study aims to demonstrate that hermeneutical approaches—particularly liberation hermeneutics and gender hermeneutics—can function as methodological instruments for rereading religious texts critically, contextually, and with an orientation toward justice. This research employs a qualitative method with a library research approach and hermeneutical analysis of Qur’anic verses and hadiths related to gender relations. The analysis focuses on QS. an-Nis?’: 34 and hadiths concerning female leadership through linguistic criticism, historical contextualization, and ethical evaluation. The findings indicate that concepts traditionally understood hierarchically, such as qiw?mah, are more appropriately interpreted as contextual responsibility rather than ontological superiority. Furthermore, hadiths that appear discriminatory toward women must be understood situationally and reoriented toward the Qur’an’s normative principles of justice and humanity. This study affirms that hermeneutics as a method of liberation is highly relevant in the Indonesian context for developing Islamic thought that is inclusive, responsive to social change, and committed to gender justice. Thus, gender reconstruction through hermeneutics is not an effort to liberalize the text, but rather an intellectual endeavor to actualize the spirit of Islamic justice in contemporary life.